EDUCATIONAL TECHNOLOGY, ITS FORMATION AND MODERN STRUCTURE - Tashmuradovna, Niyozova Yulduz; Azizovna, Djumayeva Guzal; Alimjanovna, Kadirova Dilafruz; Dilafruz Ismatullo qizi, Jabborova (International Journal of Psychosocial Rehabilitation, 2020)
This article highlights the importance of educational technologies in teaching all the subjects. In order to efficient usage of these technologies, it is important to identify their formation, structure and components. This helps teachers to disseminate best practices into academic groups more effectively. Some important point on this process will be analyzed briefly in this article.